IMPLANTACIÓN DE UN SISTEMA CONTABLE EN LA LUBRICADORA HODACAR DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA, PERIODO. DEL 01 DE ENERO AL 31 DE MARZO DEL 2017 - Gómez Maza, Janina Yesenia (2018)
VThe present work of thesis named: IMPLANTATION OF A COUNTABLE SYSTEM IN THE LUBRICATING HODACAR OF THE CANTON CATAMAYO, LOJA PROVINCE, PERIOD. OF 01 GIVE JANUARY ON MARCH 31, 2017, It is a work that represents the development of the application of a countable system adapted to the company, to determine in a royal way the economic situation in the one that is, offering a significant contribution to proprietary Ms Rosa Elizabeth Bustamante Jiménez, for the correct and opportune capture of decisions. Giving the fulfillment to the general aim of the project of thesis there was realized the implantation of a countable specific system for the lubricating Hodacar by a period of three months. For the fulfillment of the first specific aim: I initiate with a general study of the lubricating one that allowed the physical verification of the goods, rights and obligations to know the exact quantity of monetary resources that it possesses on having initiated his activities. For the fulfillment of the second specific aim: I initiate with the compilation and organization of the information obtained on the basis of the documentation source.5 For the fulfillment of the third specific aim: After analyzing and to synthesize the obtained information one proceeded to the production of the memorandum of operations; the countable process developed proceeding with the record of the transactions in the daily book, major books, trial balance, leaf of work up to the obtaining of the financial statements that reflect a loss of $ 644,74. Finally, one concludes that the accounting is a fundamental axis to improve the administration of the company, by it there is recommended to the owner to consider the implantation of a countable system that there appears in the present work of thesis, which will help him to obtain effective information of the realized operations and hereby to know the financial and economic situation of the lubricating one that it will allow him to choose for corrective policies in favour of the same one.